Identification of signaling pathways associated with achaete-scute homolog 1 in glioblastomas through ChIP-seq data bioinformatics - Zhang, Na; Zhang, Jie; Liu, Zhihong; Li, Tushuai (Frontiers in Genetics, 2022)
Achaete-scute homolog 1 transcription factors were important in the differentiation of neuronal-like glioblastomas (GBM) cancer stem cells (CSCs). To gain a better understanding the role of ASCL1 in GBM, chromatin immunoprecipitation followed by high throughput sequencing (ChIP-seq) data was analyzed to construct their gene transcription regulation network. GSE87618 were downloaded from the database of Gene Expression Omnibus. The filtered clean reads were mapped to the human genome using the software of bowtie2. Then, differential peak analysis was performed by diffbind. Finally, the annotated genes functions and signaling pathways were investigated by Gene ontology function and kyoto encyclopedia of genes genomes (KEGG) pathway enrichment analysis. Moreover, protein-protein interaction network (PPI) analysis of genes obtained from ASCL1 was carried out to explore the hub genes influenced by ASCL1. A total of 516 differential peaks were selected. GO analysis of functions revealed that promoter, untranslated region (UTR), exon, intron, and intergenic genes were mainly enriched in biological pathways such as keratinization, regulation of cAMP metabolic process, blood coagulation, fibrin clot formation, midgut development, and synapse assembly. Genes were mainly enriched in KEGG pathways including pentose phosphate pathway, glycosphingolipid biosynthesis- globo and isoglobo series, ECM-receptor interaction, and adherens junction. In total, 244 nodes and 475 interaction pairs were included in the PPI network with the hub genes including EGFR, CTNNB1, and SPTAN1. EGFR, SPTAN1 and CTNN1B might be the potential down-stream genes of ASCL1 in GBM development, and CTNN1B might take part in GBM progression based on regulating the cAMP pathway.